Implications of decadal to century scale glacio‐hydrological change for water resources of the Hood River basin, OR, USA. Issue 23 (2nd August 2016) - Frans, Chris; Istanbulluoglu, Erkan; Lettenmaier, Dennis P.; Clarke, Garry; Bohn, Theodore J.; Stumbaugh, Matt
Abstract: In glacier‐fed rivers, melting of glacier ice sustains streamflow during the driest times of the year, especially during drought years. Anthropogenic and ecologic systems that rely on this glacial buffering of low flows are vulnerable to glacier recession as temperatures rise. We demonstrate the evolution of glacier melt contribution in watershed hydrology over the course of a 184‐year period from 1916 to 2099 through the application of a coupled hydrological and glacier dynamics model to the Hood River basin in Northwest Oregon, USA. We performed continuous simulations of glaciological processes (mass accumulation and ablation, lateral flow of ice and heat conduction through supra‐glacial debris), which are directly linked with seasonal snow dynamics as well as other key hydrologic processes (e.g. evapotranspiration and subsurface flow). Our simulations show that historically, the contribution of glacier melt to basin water supply was up to 79% at upland water management locations. We also show that supraglacial debris cover on the Hood River glaciers modulates the rate of glacier recession and progression of dry season flow at upland stream locations with debris‐covered glaciers. Our model results indicate that dry season (July to September) discharge sourced from glacier melt started to decline early in the 21st century following glacier recession that started early in the 20th century. Changes in climate over the course of the current century will lead to 14–63% (18–78%) reductions in dry season discharge across the basin for IPCC emission pathway RCP4.5 (RCP8.5). The largest losses will be at upland drainage locations of water diversions that were dominated historically by glacier melt and seasonal snowmelt. The contribution of glacier melt varies greatly not only in space but also in time. It displays a strong decadal scale fluctuations that are super‐imposed on the effects of a long‐term climatic warming trend. This decadal variability results in reversals in trends in glacier melt, which underscore the importance of long‐time series of glacio‐hydrologic analyses for evaluating the hydrological response to glacier recession. Copyright © 2016 John Wiley & Sons, Ltd.